A new caruncle-bearing Limnonectes (Anura: Dicroglossidae) from northeastern Thailand - Aowphol, Anchalee; Rujirawan, Attapol; Taksintum, Wut; Chuaynkern, Yodchaiy; Stuart, Bryan L. (Zootaxa, 2015)
A new species of the dicroglossid frog genus Limnonectes is described from Ubon Ratchathani Province, northeastern Thailand. Limnonectes lauhachindai sp. nov. differs from its congeners by having males with a low-profiled, U-shaped caruncle with free posterior margin that completely occupies, but does not extend beyond, the interobital region. The new species is most closely related to L. gyldenstolpei and L. dabanus. Its description brings the total number of caruncle-bearing species of Limnonectes to five.